2018
DOI: 10.1002/fsn3.763
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the effects of different high‐temperature treatments on texture and aroma characteristics in Alaska pollock surimi

Abstract: This study tested the gel properties, quality of Alaska pollock surimi subjected to different temperature treatments. Results showed that when the heating temperature is 110°C, the water‐holding capacity (WHC) and texture of the surimi and gel strength increased, but as the heating temperature increased, the gel strength decreased significantly (p < 0.05), and ultimately destroyed. The heating temperature had no significant effect on the whiteness of the surimi gel, although it did have a significant effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Temperature was the main factor contributing to the differences in aroma between the treatment groups of samples. Zhang et al [ 42 ] revealed that the heat-treatment temperature had a significant effect on the volatile components in surimi gels, which was further confirmed by the results of this study. In practice, however, this reaction is complex and is influenced by a number of factors.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Temperature was the main factor contributing to the differences in aroma between the treatment groups of samples. Zhang et al [ 42 ] revealed that the heat-treatment temperature had a significant effect on the volatile components in surimi gels, which was further confirmed by the results of this study. In practice, however, this reaction is complex and is influenced by a number of factors.…”
Section: Resultssupporting
confidence: 89%
“…In addition, the yellow-green value (b*) of the BAC was significantly higher than that of the other treated samples, indicating their overall yellow color. Some studies have shown that the color of surimi products gradually changes from white to pale yellow after high temperature and pressure treatment [ 42 ]. According to the qualitative analysis results of volatile compounds in samples of each treatment group in this study, it was found that the detection intensity of furan flavor substances in BAC was significantly higher ( p < 0.05) than samples of other treatment groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total contribution rate was 98.82%, which was greater than 95%, indicating very minor interference. 32 When the ratios of anchovy mince to silver carp surimi were 0/100 and 100/0, the contribution rate of the rst principal component in both cases showed the biggest difference. With the increase in anchovy mince content, the PC1 of the blended systems increased gradually.…”
Section: Electronic Nosementioning
confidence: 93%
“…The aldehydes content is usually lower than that of the other compounds, and account for a fatty avor. 32 Hexanal is the product of linoleic acid oxidation, with the smell of raw oil, green grass and apple. When the ratios of anchovy mince to silver carp surimi were 10/90, 20/80 and 30/70, the content of the blended systems aldehydes were higher, which was consistent with the previous results.…”
Section: Electronic Nosementioning
confidence: 99%